Pengaruh Kesadaran Pajak dan Pengetahuan Pajak terhadap Kepatuhan Wajib Pajak pada Karyawan PT Surveyor Indonesia - Cahyo Hadi Arrosyid; Bambang Soedaryono (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aims to determine the influence of tax awareness and tax knowledge on taxpayer compliance of PT Surveyor Indonesia employees. This research uses quantitative methods with a sample of 98 respondents. The results of this research indicate that tax awareness has a significant influence on taxpayer compliance of PT Surveyor Indonesia employees. Tax knowledge has a significant positive influence on taxpayer compliance of PT Surveyor Indonesia employees. Tax awareness and tax knowledge, both together and individually, have a significant positive effect on taxpayer compliance of PT Surveyor Indonesia employees.